Clima do Cerrado: dinâmica atmosférica e características, variabilidades e tipologias climáticas: Cerrado climate: atmospheric dynamics and features, variability and climatic typologies (Élisée - Revista de Geografia da UEG, 2020)
This text seeks to demonstrate an overview of climatic aspects of Cerrado, addressing the dynamics of atmospheric systems and the climatic features, variability and typologies of this biome. To this purpose, the text was developed, at first, from a bibliographic review about the properties and dynamics of atmospheric systems operating in the area in question. In a second step, secondary data were used, with different spatial and temporal cutouts, for the description of the spatio-temporal variation of the main climatic elements (temperature, precipitation and humidity) of the biome; the portrayal of the annual, monthly and daily variability for a locality located in the core area of ​​the Cerrado (Goiânia-GO) and; the definition of climatic typologies for the biome. The data presented show a strong climatic seasonality, configuring a rainy period, during spring and summer, which is interspersed with a dry period, throughout autumn and winter. Under the influence of the variation of latitude and altitude, the northern portion of the biome has the highest temperatures, whereas, in response to the performance of atmospheric systems that produce rain and are responsible for the transport of humidity, the averages of precipitation and relative humidity decrease in northwest/southeast direction. Still, it is noticeable the variability between the annual accumulated and the monthly precipitation regime and, especially, regarding the daily rhythm of the meteorological elements, based on the city of Goiânia - evidencing the role of the performance of the atmospheric systems in the genesis and variability of the types of weather. Units were subdivided up to the level of climatic types, expanding the traditional proposals of climatic classifications, detailing their spatial location in the Brazilian territory. Empirical and genetic models were able to associate themselves in an exchange of information, and generated a pattern that addresses both the observed values ​​of weather and climate, and the influence of atmospheric systems.
Keywords: Cerrado; Climatology; Atmosfpheric Dynamics; Variability; Climate Classification